Creating a new consensus on population : the politics of reproductive health, reproductive rights, and women's empowerment - Singh, Jyoti Shankar, 1935- (London : Earthscan, 2009)
"Population growth, reproductive health and reproductive rights are amongst the most pressing issues facing governments and the international community. Since the world's governments agreed for the first time on far-reaching and enlightened population policies at the 1994 International Conference on Population and Development (ICPD) in Cairo, a good deal of progress has been made on these issues, but major challenges remain. This fully updated edition of Creating a New Consensus on Population charts international progress on efforts to address population and development, reproductive health, reproductive rights, religion, contraception and the empowerment of women. Historical coverage includes the lead up process to the ICPD, the conference itself and the global consensus and the ICPD Programme of Action that resulted. The book then turns to how population issues have developed over the past decade and a half including follow-up and implementation at the international level by the United Nations Population Fund (UNFPA) and other UN agencies and organizations. Key international events are covered including the 1999 ICPD+5, Millennium Summit 2000, ICPD+10 and the 2005 MDG+5 as well as relevant regional events. The book also examines the reorientation of policies and programmes and implementation at national levels across the world. Crucially, it looks at emerging issues and partnerships including the increasing role of NGOs, women's groups, youth groups, foundations, public-private partnerships and other non-state stakeholders."--Publisher's description.
Bucharest, Mexico and Cairo -- From family planning to reproductive health -- Population and development -- The empowerment of women -- Partnership with the non-governmental sector -- Mobilizing resources for population programmes -- The Cairo agenda and the international community -- Institutional response -- Implementing the Cairo agenda.
Includes bibliographical references (p. 227-234) and index.
Keywords: Population policy; Population